ANALISIS KELAYAKAN PENGEMBANGAN AGROINDUSTRI GULA KELAPA SKALA MIKRO DI KABUPATEN LAMPUNG TIMUR - Peni Rosepa; Muhammad Irfan Affandi; Rabiatul Adawiyah Adawiyah (Lampung University, 2014)
This study aims to: ( 1 ) analyze the feasibility of coconut sugar agro-industry profitable or not for craftsmen coconut sugar ( 2 ) analyze the effect of changes in the cost of producti, the selling price of sugar palm , and coconut sugar production decline. The experiment was conducted in the Village District of the State Supreme Margatiga East Lampung regency. Location research intentionally ( purposive ) with the consideration that the East Lampung district is a center of coconut production in Lampung Province. The number of respondents were 35 farmers and to determine the respondents was used census method. The first goal was answered using financial analysis and the second goal was answered using sensitivity analysis. The results showed that (1) coconut sugar Agro-industry in the District Court Margatiga Rural Affairs feasible to be developed, with each having the IRR was 54 % ( 2 ) coconut sugar Agro-industry in the State Supreme has good prospects to be developed and commercialized. With the borrowing rates of 22% can remain viable at the time of the increase in production costs and a decrease in production by 4.28 % and 12 % and at the time of the sale price decline of 10% from the technical and production aspects have enough raw materials available in the local area.Key words: Agro-industry, Coconut Sugar , Financial